INNV-18. THE AVAILABILITY AND ROLE OF CLINICAL PHARMACISTS IN THE AMBULATORY NEURO-ONCOLOGY SETTING: AN INTERNATIONAL SURVEY. (11th November 2019) - Patel, Mallika; Lipp, Eric; Miller Patrick Healy, Elizabeth; Herndon, James; Peters, Katherine
Abstract: BACKGROUND: Outpatient clinics treating neuro-oncology patients are becoming more multidisciplinary. Utilization of all team members is critical for the holistic care of these complex patients. Specifically, the role of a clinical pharmacist in the ambulatory multidisciplinary clinic remains undefined and will likely evolve as more therapeutic options are developed to treat central nervous system malignancies. We queried the Society for Neuro-Oncology (SNO) membership about the availability of a clinical pharmacist in their ambulatory setting and, if present, the role of that clinical pharmacist. METHODS: In an IRB exempt study, we surveyed the SNO community (targeting primarily clinicians) and analyzed responses to queries about clinical pharmacists in the ambulatory neuro-oncology setting. RESULTS: Of the 65 SNO members who responded, 52 of these were clinical members. Of these 52 clinical members, the majority were physicians (88.5%, n=46). Of these 46 physicians, most were in academic practices (93.5%, n=43). Over half of the 52 clinical respondents (51.9%, n=27) reported that they saw ≥ 30 primary brain tumor patients a month, thus typifying busy clinical neuro-oncology ambulatory clinics. Despite having busy clinics, only 12 (28.6%) of the 42 providers with access to a clinical pharmacist reported that their clinical pharmacist was solely dedicated to neuro-oncology patients. For the respondents who had access to a clinical pharmacist, only 28 (66.7%) of those pharmacists had direct patient interaction in the clinic. The top three roles of the clinical pharmacist included medication review (81%, n=34), chemotherapy dosing and modifications (73.8%, n=31), and practice guideline development (61.9%, n=26), none of which are associated with direct patient interaction. CONCLUSIONS: We found that while our surveyed population of SNO clinical members have demanding outpatient neuro-oncology practices, most do not have the support or expertise of dedicated neuro-oncology clinical pharmacists.